OP0132 Structural and microstructural intra-articular bone changes at the metacarpal heads in patients with psoriatic arthritis compared to controls: a hr-pqct study. (12th June 2018) - Wu, D.; Griffith, J.F.; Lam, S.H.; Wong, P.; Yue, J.; Shi, L.; Li, E.K.; Cheng, I.T.; Li, T.K.; Zhu, T.Y.; Hung, V.W.; Qin, L.; et al.
Abstract : Background: Located inside the joint capsule, 1 the entire metacarpal head (MCH) is directly exposed to intra-articular inflammatory milieu in patients with psoriatic arthritis (PsA). We hypothesise that bone loss and new bone formation in the MCH will be more prominent in PsA compared to healthy controls. Objectives: To investigate structural (bone erosion and enthesiophyte) and microstructural intra-articular bone changes in patients with PsA at the second and third MCH (MCH 2 and 3) compared with controls. Methods: 139 subjects (77PsA, 62 control) underwent HR CT scanning at the MCH 2 and 3 and distal radius. 15 patients with joint destruction 2 were excluded from further analysis. An integrative CART-EBEE approach was developed to investigate the structural and microstructural bone changes. CART method (AB) was used to calculate volume of bone erosion and enthesiophyte [Crop of metacarpal bone(a, b); Automated segmentation of periosteal surface (c, e);Restoration of the missing cortical boundary based on anatomic curve(d, f);Three-dimensional calculation of volume(g)]; EBEE method was used to calculate volumetric bone mineral density (vBMD) and microstructure before and after exclusion of Bone Erosion (C) and Enthesiophyte (D). Results: 62 patients with PsA and controls were comparable in age, gender and body mass index. PsA patients had a significantly increased number (mean ±SD/patient 2.4±1.4 vs 1.3±1.1, p<0.001) and total volume of enthesiophytes (8.75±6.92 vs 4.36±4.90 mm 3, p<0.001); but a similar number of bone erosion (mean ±SD/patient 2.9±1.2 vs 2.7±1.4, p=0.408) and a trend suggestive of an increase in total volume of bone erosion (11.88±7.82 vs 9.64±5.96 mm 3, p=0.076) per person compared with control. Depth of each individual bone erosion was greater in PsA than control; while no differences in the maximal height of each individual enthesiophyte was found between PsA and control. With regards to the microstructure, PsA showed a significantly decreased total vBMD, cortical vBMD (Ct.vBMD) and Ct. thickness at the distal radius; while a preferential bone loss at the trabecular (Tb.) compartment [Tb. vBMD; trabecular bone volume fraction [BV/TV] and Tb. thickness] was observed at the MCH compared to control. After excluding of enthesiophyte, a further deterioration in the Ct. compartment (vBMD, perimeter, thickness) in PsA patients was observed. Regression model in PsA and controls indicated that PsA was independently associated with an increased total volume of enthesiophytes per person. Regression model in PsA showed that CRP, older age and higher BMI were independently associated with an increase in the total volume of bone erosion. On the other hand, older age was independently associated with an increase in total volume of enthesiohyte per person. Conclusions: Intra-articular trabecular bone loss and entheseal new bone formation was more prevalent in the MCH of patients with PsA. References: [1] Simon D, et al. J Bone Miner Res2017;32:722–730. [2] Stach CM, et al. Arthritis Rheum2010;62:330–9. Disclosure of Interest: None declared